Gæld i Gram herred. Lån, kredit og pengeøkonomi i det nordlige Sønderjylland før og efter katastrofen 1657-6 - Rasmussen, Carsten Porskrog (Historisk Tidsskrift, 2013)
Debt in Gram District Loan, Credit and Money Economy in Schleswig before and after the 1657-60 DisasterThe present article deals with credit relations among peasants in the seventeenth century, more specifically, in Gram District (herred in Danish) in the northern half of the Duchy of Schleswig. Here, virtually all the peasants were freeholders or crown tenants and since 1632 generally exempt from labour service. Their most important obligations to the Crown were stipulated in monetary tariffs: partly rents and dues, partly incremental taxes. Generally, this means that the economy in this respect was more monetarized than in the Kingdom of Denmark, where rents in kind and labour service were prevalent. Gram District was severely affected by the 1657-60 war. The district not only suffered from the contributions extorted by occupational troops, but also from devastation, plunder, and an epidemic that wiped out large portions of the population. After the war, two-thirds of the farms and houses lay desolate, and it took many years for the district to fully recover. The study throws light on credit conditions before and after the war. It is true that the source material is from the post-war period, consisting, as it does, of court records from 1661 and 1667-70, but the 1661 court records contain a number of estate assessments and evaluations of assets and liabilities of abandoned farms that afford insights into pre-war credit conditions. There was a widespread credit system in Gram District before the war. Most by far of the examined estates and assessments reveal debt relations, and of these the greater part was between peasants, while tax and rent arrears and debts to town merchants played a minor role. A number of debts were the result of sibling inheritance claims. To be sure, only freeholders owned land, but all peasants owned farm buildings, which together with stock, furnishings and the like represented considerable values to be divided among the heirs. The problem of division was often solved by the heir to the farm issuing bonds to the other heirs. Where the details of this arrangement are known, and mostly they are not, it was normal to pay interest, if the heir was of age. Inheritance is far from the only explanation of debt relations. Approximately a third of the examined estates contain a number of debt items, in round figures, to other peasants, often documented with a bond (obligation in Danish). Furthermore, the sources show that a large group of peasants owed money to a smaller group. In some cases it is explicit that the money was lent with interest, while in various other cases this is implied in the debt relation patterns. It appears that there was a number of active moneylenders spread throughout the district. They lent money on interest, normally within a limited geographical area, typically a couple of parishes. The money market was thus quite local, and the interest rate fixed; it was none the less a money market. A rather large segment of the peasants figured as borrowers in this credit market, while others appear to have had only the credit relations that derived from inheritance or tax and rent arrears, merchant credit, etc. After the war, property rights and credit claims were remembered, recorded and formally recognized despite the disastrous condition of the district, and this was to a large extent facilitated by surviving bonds. On the other hand, it is clear that very many debtors or their heirs were incapable of paying their debts. Assessments of abandoned farms and various estates functioned in practice as bankruptcies, where property was turned over to a new owner, who incurred a debt corresponding only to assets. Ten years after the war the debt patterns of the surviving peasants were not much different from those reflected in the estates from 1661. However, two changes can be seen. Firstly, there is a greater frequency of tax and excise arrears. Secondly, the largest debts between peasants were old, pre-war debts, and in many instances default on interest went all the way back to the war. This shows that the legal system was still intact, but that the credit market was in deep crisis. After the war, only one notably active moneylender is to be found: the Justice of the Peace (herredsfoged in Danish). Translated by Michael Wolfe